First discovery of parasite eggs in a vertebrate coprolite of the Late Triassic in Thailand - Nonsrirach, Thanit; Morand, Serge; Ribas, Alexis; Manitkoon, Sita; Lauprasert, Komsorn; Claude, Julien (PLOS ONE, 2023)
A paleoparasitological investigation of a vertebrate coprolite from the Huai Hin Lat Formation (Upper Triassic) was carried out. Five morphotypes of potential parasite eggs or sporocysts were identified in the coprolite by microscopic analysis using thin section technique. The rounded or oval shape and thick shell of one of the five morphotypes suggests that it belongs to nematode of the order Ascaridida. Systematic assignment of other morphotypes cannot be done in detail but suggests that the host was parasitized by different species of parasites. This is the first record of parasites in terrestrial vertebrate hosts from the Late Triassic in Asia and it provides new information on parasite-host interactions during the Mesozoic era.